1994
DOI: 10.1161/01.cir.90.1.264
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of ventricular tachycardia after surgical repair of tetralogy of Fallot. Relation between intraoperative mapping and histological findings.

Abstract: The results of this study indicate that patients with VT after radical correction of the TF have abnormal histopathological findings at the site of the prior right ventriculotomy scar. These lesions were noted within the region of delayed activation found during epicardial mapping and were found to be a part of the reentrant circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…10 In agreement with our findings, previous reports also have found VT to be due to macroreentry. 4,5,7 Misaki et al 6 described activation revolving around a myotomy scar with diastolic activity within the lateral RVOT wall consistent with the most common location of reentry circuit isthmuses in the present study.…”
Section: Previous Studiessupporting
confidence: 85%
See 1 more Smart Citation
“…10 In agreement with our findings, previous reports also have found VT to be due to macroreentry. 4,5,7 Misaki et al 6 described activation revolving around a myotomy scar with diastolic activity within the lateral RVOT wall consistent with the most common location of reentry circuit isthmuses in the present study.…”
Section: Previous Studiessupporting
confidence: 85%
“…RV incision and myectomy produce RVOT aneurysmal or akinetic regions in Ͼ50% of the patients. 27 Misaki et al 6 found surviving myocytes embedded in fibrous tissue in resected tissue from an RVOT region with delayed conduction, resembling the histological findings in the border zone of infarcted myocardium. 6 Of interest, the postmortem specimen of the patient who survived 5 years after repair showed extreme thinning only of the anterolateral RVOT, consistent with isthmus 1 (Figure 4e).…”
Section: Previous Studiesmentioning
confidence: 78%
“…12 Postrepair VT in the setting of TOF was originally classified as arising from both the OT and from the septal-inflow area of the RV where fractionated electrograms were commonly observed with their induction. 21,26,27 Follow-up studies based on excision of ventricular tissue at the time of arrhythmia surgery also demonstrated prominent fibrosis with subendocardial islets of surviving myocytes in the region of the RVOT. 21 The inclusion of a group of cases surviving surgical repair in the present analysis afforded an opportunity to evaluate these findings and confirm their consistent presence in the ventricular conduction isthmuses that have been more recently described in TOF.…”
mentioning
confidence: 98%
“…Isthmus 2, between the ventriculotomy and pulmonary annulus, was frequently described in the literature as a target for catheter ablation. [21][22][23][24] However, this isthmus was often absent secondary to a transannular incision or avoidance of RVOT incision altogether, and it is likely that with changes in surgical technique this isthmus will be encountered even less frequently with time. 4,6 Likewise, isthmus 4 was seen only occasionally and was noticeably uncommon in the older surgical survivors in the present series.…”
mentioning
confidence: 99%
“…It is believed that a fraction of late arrhythmias in rTOF patients are acquired due to the formation of myocardial substrate caused by fibrotic scars after the repairing surgery [12,13]. Other long-standing risk factors are chronic pulmonary regurgitation (PR) and right ventricular outflow tract (RVOT) aneurysm which commonly coexist and have a proarrhythmic role [11].…”
Section: Late Arrhythmia In Rtof Patientsmentioning
confidence: 99%